MASA DEPAN POLITIK ISLAM - Zainuddin Syarif (Millah: Journal of Religious Studies, 2013)
Integration between Islam and politics can not be denied, because Islam essentially is a perfect beliefs and teachings that not only teach about worship alone, but also it set all aspects of human life; politics, economics, and social. Islam deal with religion and the world, because Islam is ad-dien wa ad-daulah that regulates worship and muamalah. That is the essence of political leadership as “hirasah al-dīnwa siyāsah al-dunyā”.